Respons Pertumbuhan Planlet Kentang (Solanum tuberosum L.) ‘Granola’ Terhadap Pemberian Polyethylene Glycol (PEG) 6000 Secara In Vitro - Yulia Puspita Dewi; Endang Nurcahyani; Sri Wahyuningsih; Yulianty (CV. Multi Kreasi Media, 2025)
Potato (Solanum tuberosum L.) is one of the horticultural crops with strong potential as an alternative carbohydrate source. As the human population increases, the demand for potatoes continues to rise; however, its growth and productivity are often constrained by unfavorable environmental conditions, particularly drought stress. Polyethylene Glycol (PEG) is an osmotic agent commonly used to simulate drought stress in plants under in vitro conditions. This study aimed to determine the effects of PEG 6000 and to identify the PEG concentration that remains tolerable for potato plantlet growth under in vitro drought stress. The experiment was arranged in a Completely Randomized Design (CRD) with a single factor, consisting of PEG concentrations of 0%, 5%, 10%, 15%, and 20%, each with five replications. The observed parameters included plantlet survival, plantlet height, and stomatal index. Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by the Honestly Significant Difference (HSD) test at 5%. The results showed that PEG 6000 significantly reduced plantlet height and stomatal index. The tolerable concentration of PEG 6000 for potato plantlets was determined to be 15%.